Effects of Water Stress on the Agromorphological Parameters of Two New Maize (Zea mays L.) Lines (L36 and L71) Obtained from the Variety EV8728 - Néné-bi, François Zaouli; Turquin, Louise; Konan, Séraphin Kouakou; Soro, Dogniméton; Ayolie, Koutoua; Bléhou, Clotaire Edja; Kouadio, Justin Yatty (European Scientific Journal, ESJ, 2022)
Maize (Zea mays L.) or Indian wheat is the most cultivated cereal in the world and the first in terms of quantity before wheat. Its cultivation is confronted with the climate change which causes drought, and this last one reduces considerably its production. The objective of this experiment is to select maize (Zea mays L.) varieties resistant to water stress using gamma irradiation. Its aim is to characterize agromorphologically two maize lines derived from the gamma irradiated variety EV8728. This study took place in Daloa (Ivory Coast). The plant material consisted of maize plants obtained by self-fertilization after five cycles from seeds of the variety EV8728 irradiated with gamma rays at a dose of 300 grays. Observations and measurements were made on the number and area of leaves, height and diameter of maize plants, male and female flowering parameters (date of panicle appearance, pollen grains, cob and silks) and number of spikelets, cob insertion height (CIE), panicle height and internode length. At the 58th das, the highest number of leaves (18.76) was observed in the plants of line 36 watered at capacity in field S0. On the other hand, the number of leaves (16.04) was lowest on the plants of the same line under severe stress (S2). Regardless of the type of stress applied, the plants of the control EV8728 always dominate, while the most stunted are those of the line L36. The date of panicle appearance (DAP) was early with the EV8728 control compared to the tested lines (L36 and L71), while the date of pollen appearance (DAGP) was about 4 d after the panicle was visible. Under moderate stress, a delay in flowering (anthesis) is observed in EV8728 and line L71 while there is no change in date for line L36.